Avaliação e estimativa de recarga dos aquíferos da região da APA Carste de Lagoa Santa, MG - Gabriela Meira Teixeira (2023)
The Karst Environmental Protection Area (EPA) of Lagoa Santa is a place of great environmental and scientific significance, where essential aquifers formed by carbonate rocks from the Bambui basin are stored, playing a fundamental role in supplying water to the region's population, both public and private. This area is located in the state of Minas Gerais, Brazil, and despite its significant environmental relevance, it faces challenges related to the increasing environmental impacts caused by human activity. Therefore, it is crucial to conduct studies that analyze the interaction between surface and groundwater in this region. In this regard, this work aimed to estimate aquifer recharge in the region using four different methods: the recession curve displacement method by Rorabaugh (1964), the digital recursive filter method developed by Lyne and Hollick (1979) and automated by Smakhtin (2001), the method based on water level variation in observation wells by Healy and Cook (2002), and a fourth method based on indirect acquisition of recharge indices through the overlay of parameter categorization maps influencing recharge, called APLIS by Andreo et al., (2004), which was adapted for application in the studied karst. The application of more than one method aimed to compare the results and define the advantages and weaknesses of each one when applied to the specific conditions of the study area. Validation of monitoring data and key streamflow curves for the main streams in the area was also carried out, along with a characterization of the hydrographic basins and their behavior in response to rainfall events. In addition to quantitative analysis, this work characterized and zoned the main recharge areas in rock masses, karst depressions, soil cover areas, and by lithotype. The average annual recharge rates obtained by the recession curve displacement, digital recursive filter, water level variation, and adapted APLIS methods were, respectively, 13%, 9%, 9%, and 16%. The high pumping rates in the region suggest underestimated recharge values using direct monitoring data. Among the recharge methods using basin discharge data, the Rorabaugh (1964) method showed higher accuracy because it uses daily flow measurements. However, the Lyne and Hollick (1979) method automated by Smakhtin (2001), even using a monthly flow database, proved to be applicable for longer monitoring periods. The water level variation method and APLIS were useful for better zoning of recharge indices. This work was relevant for proposing recharge estimation using different methodologies and databases, allowing the replication of these techniques, even in regions where there is no physical monitoring. Therefore, these methods are useful for adoption by public or private organizations, especially in remote areas or where there are no investments or projects for monitoring network implementation.